ISLAM DAN INDONESIA ABAD XIII-XX M DALAM PERSPEKTIF SEJARAH HUKUM - Fadhly, Fabian (Faculty of Law, Parahyangan Catholic University, 2017)
Islam and Indonesia are a mutually supportive part of both, the reality of history shows the circumstances. Islam became part of Indonesia that was known at that time as the archipelago, the various Islamic teachings seep into a part of Indonesian society. Law as one of his teachings known as fiqh, then translated into Islamic law in the context of Indonesia today. Islamic law experienced a long journey from the era of the sultanate to the modern era, with various changes and developments follow the times and needs of the society of Islamic law itself. The method put forward in this paper is a historical method with a juridical approach. The demarcation of time and time that permeates Islam from time to time in extending its influence, to the various behaviors of Indonesian society through the long historical journey. The timing also indicates that Islam is a part of synergy through Islamic law with Indonesian society (Nusantara), as the context of the understanding or adaptive transformation of fiqih that emerges and develops in the Sultanate era as a form of manifestation of fiqh in the classical period.